2001
DOI: 10.1111/1532-7795.00004
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Relational Support in Adolescence: Dimensions, Configurations, and Adolescent Adjustment

Abstract: The perceived relational support from four key providers (father, mother, special sibling, and best friend) on five provisions (quality of information, respect for autonomy, emotional support, convergence of goals, and acceptance) was examined for 2,262 adolescents (aged 12-18 years). In a variablecentered approach, factor analyses yielded five dimensions of support: three specific to providers (parent, friend, and sibling support) and two specific to provisions (convergence of goals and respect for autonomy).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
203
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 37 publications
13
203
1
11
Order By: Relevance
“…To assess parental support, participants completed a 12-item version of the Relational Support Inventory (RSI; Scholte et al 2001). The scale measures aspects of emotional and instrumental support by fathers and mothers separately.…”
Section: Perceived Parental Supportmentioning
confidence: 99%
“…To assess parental support, participants completed a 12-item version of the Relational Support Inventory (RSI; Scholte et al 2001). The scale measures aspects of emotional and instrumental support by fathers and mothers separately.…”
Section: Perceived Parental Supportmentioning
confidence: 99%
“…Cronbach's reliability coefficients for these subscales were .87, .76, and .75, respectively. Scholte, van Lieshout, & van Aken, 2001). Perceived support from parents, best friend, and boy/girlfriend was assessed using this 27-item scale which measures the following four dimensions: emotional support (e.g., "In this person's view, I can't do anything right: He/she is always criticizing me;" reverse coded), informational support (e.g., "This person explains or shows how I can make or do something"), respect for autonomy (e.g., "This person lets me solve problems as much as possible on my own but also provides help when I ask for it"), and convergence of goals (e.g., "This person and I have many conflicts with regard to school achievement, the future, or career opportunities;" reverse coded).…”
Section: Father-mother Aggressionmentioning
confidence: 99%
“…The RSI measure of social support has been found to be positively associated with personal adjustment in adolescence (Branje, van Aken, & Lieshout, 2002;Scholte et al, 2001) and negatively with psychological distress in the Spanish adolescent population (Herrero et al, in press). The Father-Mother Aggression Scale has been used in previous investigations (e.g., Estévez & Musitu, 2004), in which higher levels of aggression between parents were found to be related to higher levels of aggressiveness in children.…”
Section: Adolescent-family Inventory Of Life Events and Changesmentioning
confidence: 99%
“…Results of other studies conducted on samples of TD adolescents indicated that self-efficacy (Jacobs et al, 2002;Pajares & Valiante, 1999) and optimism (Carvajal et al, 2002, Patton et al, 2011 decreased with age, and that seeking help as a coping strategy occurred earlier than more complex strategies requiring more developed cognitive abilities (Compas et al, 2001;Hampel & Petermann, 2005). With regard to sense of relatedness in TD adolescents, previous studies also indicated that younger adolescents had a higher level of attachment (Laible et al, 2000;Muris et al, 2003) and perceived social support (Malecki & Demaray, 2002;Scholte et al, 2001), as well as a lower level of loneliness (Brage et al, 1993;Chipuer & Pretty, 2007) compared to older adolescents. The obtained results which point to age differences in emotional reactivity in TD adolescents are consistent with findings of other authors according to which emotional reactivity decreased (Silket al, 2003), and emotion regulation increased (Silvers et al, 2012) with age.…”
Section: Discussionmentioning
confidence: 97%